Recycling of water treatment plant sludge for copper adsorption from aqueous solutions - Anggrika Riyanti; Hadrah Hadrah; Arisanti Monica Zeusica Sihombing (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Recent studies have explored various adsorbent materials that are low-cost, available in quantity, and effective for heavy metal removal, one of them is the Water Treatment Plant (WTP) sludge. The study aimed to investigate the potential of recycling Water Treatment Plant sludge into an adsorbent for Cu (II) removal. The sludge adsorbent was carbonized by using a furnace at 600°C for 2 hours. This study was conducted in batch. The adsorbent effectiveness was analyzed by varying the dosage, contact time, and activation of the sludge adsorbent on Cu (II) removal. The adsorption isotherm was analyzed using the Langmuir and Ferundlich models, and the kinetic study used pseudo-first-order and pseudo-second-order model. The results showed the removal efficiency of Cu (II) for both activated and non-activated sludge adsorbents reached 98.6–99.9%. The addition of dosage did not affect the increase in Cu (II) adsorption capacity. Activation of the adsorbent increased the adsorption capacity of Cu (II) with the equilibrium time at 60–90 min, shorter than the non-activated adsorbent at 90–120 min. The adsorption isotherm model for both adsorbent types fitted well to the Langmuir model, indicating the adsorption process occurs in a single layer on a homogeneous surface. The adsorption kinetics followed pseudo-second-order with a high correlation coefficient. Water treatment sludge, an industrial by-product, has the potential to be an effective and low-cost adsorbent material for Cu removal.